Delete the Border! - Ilich, Fran (Studies in Latin American Popular Culture, 2004)
This article focuses on the borders of Mexico. Cities in the north of Mexico, like Tijuana, are new. Despite the fantasy of free flow, the border instead of being in a process of dissolution, is still in a process of continuous (re)construction, both physically and psychically. Those were the days when there where still many Mexicans and Central Americans trying to get into the U.S. via Tijuana, so one would see crowds and lines of them, all the way down the international highway, people camping and so on. It was quite dangerous to walk in those places, because many of the people aspiring to cross were in complete poverty and desperation.